Defining the Influence of the Support of Bus Service on Road Safety - Poliak, Milos; Komackova, Lenka; Semanova, Stefania; Hernandez, Salvador; Jaskiewicz, Marek (Communications - Scientific letters of the University of Zilina, 2016)
The paper deals with the relationship of increasing road safety through the support of bus service. The objective of the paper is to analyse the factors affecting road safety. Subsequently, the impact of the bus service support on road safety is expressed through those factors. The paper highlights the multiplier effect of the bus service support on road safety increase. First part of the paper analyses factors affecting road safety. The factors are divided into three groups in terms of infrastructure, vehicles and drivers. Further part emphasizes the possibilities for improving individual factors under the support of bus service. The last part of the paper processes a theoretical model which reflects the impact of the bus service support on increasing road safety.